Short-term fluid temperature variations in either a coaxial or U-tube borehole heat exchanger. (May 2017) - Gordon, David; Bolisetti, Tirupati; Ting, David S.-K.; Reitsma, Stanley
Highlights: Validates a composite cylindrical model for coaxial BHEs. Model accounts for thermal heat capacity of piping material. Model accurately simulates short-term fluid temperatures within a coaxial BHE. Abstract: This paper uses composite cylindrical heat-source (CCS) models and typical thermal response test procedures to investigate two full-scale borehole heat exchangers (BHE); where one is a U-tube BHE, and the other, a pipe-in-pipe (coaxial) BHE. A previously developed CCS model is compared to a simplified infinite line-source (ILS) model. A time-varying heat-flux term is verified for the U-tube case, noting the error found when using the CCS model. A model is developed using a similar approach accounting for a coaxial configuration showing a root mean square error (RMSE) of less than 0.1 °C over the duration of the test.